Acousto-optic modulation of a fiber Bragg grating in suspended core fiber for mode-locked all-fiber lasers. (24th February 2015) - Silva, Ricardo E; Tiess, Tobias; Becker, Martin; Eschrich, Tina; Rothhardt, Manfred; Jäger, Matthias; Pohl, Alexandre A P; Bartelt, Hartmut
Abstract: The interaction of a fiber Bragg grating and longitudinal acoustic waves in a three-air-holes suspended core fiber is experimentally investigated and employed to mode-lock an ytterbium-doped fiber laser. An optimized design of an acousto-optic modulator based on two piezoelectric transducers and 1 cm grating length is also proposed. For an electrical signal strength of 10 V applied to the modulator, the results indicate output pulses with a width of less than 550 ps at a repetition rate of 10 MHz. The reduction of the grating length and the power consumed by the transducer, when compared to previous studies, points out to more efficient, compact and fast acousto-optic modulators for mode-locked all-fiber lasers.